2014
DOI: 10.1103/physrevb.90.184415
|View full text |Cite
|
Sign up to set email alerts
|

Spin wave emission in field-driven domain wall motion

Abstract: A domain wall (DW) in a nanowire can propagate under a longitudinal magnetic field by emitting spin waves (SWs). We numerically investigated the properties of SWs emitted by the DW motion, such as frequency and wave number, and their relation with the DW motion. For a wire with a low transverse anisotropy and in a field above a critical value, a DW emits SWs to both sides (bow and stern), while it oscillates and propagates at a low average speed. For a wire with a high transverse anisotropy and in a weak field… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…We now considered a classical Heisenberg biaxial chain along z direction with the DMI in an external field H 43 44 …”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…We now considered a classical Heisenberg biaxial chain along z direction with the DMI in an external field H 43 44 …”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…This process transfers energy from the DW to the domains where it is quickly dissipated. Such mechanism, neglected by the 1D model of Walker and Slonczewski, has been investigated numerically in one-dimensional systems where it has been shown that spin waves emission from the DW can take place and contribute to DW motion when a strong hard-axis anisotropy is present in the system [29][30][31] and also in in-plane magnetized permalloy strips in presence of various forms of disorder [16,32]. In our system, both disorder and the fact that the wall is extended in length play a role, as discussed below.…”
Section: Energy Dissipationmentioning
confidence: 99%
“…The Walker breakdown is related to the instability of domain walls, for example, spin waves may be emitted when a transverse DW travels in a thin strip [13,14]. Micromagnetic simulations show that a moving DW in cylindrical nanowires has an almost vanishing mass [3,15].…”
Section: Introductionmentioning
confidence: 99%
“…b) shows a contour plot of the dissipation rate ω i as a function of β and q for α = 0.02 and b = −0.15, it is found that in the top right corner ω i is negative, which indicates that β term may leads to a negative dissipation rate if |b| < 2. For the case that α = 0 and b = 0, the solution of ψ(ξ, τ ) reduces to ψ(ξ, τ ) = ψ 2 0 /2 a + iτ e i[q0ξ−(1+q 2 0 )τ ]−(ξ−2q0τ ) 2 /4(a+iτ )(14) …”
mentioning
confidence: 99%